2022
DOI: 10.1007/978-3-030-94896-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics in Helium Droplets

Abstract: Helium nanodroplets are peculiar systems, as condensed superfluid entities on the nanoscale, and as vessels for studies of molecules and molecular aggregates and their quantum properties at very low temperature. For both aspects, the dynamics upon the interaction with light is fundamental for understanding the properties of the systems. In this chapter we focus on time-resolved experiments in order to study ultrafast dynamics in neat as well as doped helium nanodroplets. Recent experimental approaches are revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 265 publications
0
2
0
Order By: Relevance
“…He N are nanometer-sized superfluid containers that can be loaded with a wide variety of dopant atoms or molecules to study electron–atom/molecule–photon interactions inside a quantum solvent. In addition to the low temperature of 0.4 K, He N feature unique solvent properties: (i) They have the lowest influence on solvated particles both in the electronic ground state and upon photoexcitation, , (ii) they can be loaded with multiple dopant atoms and molecules by the pickup technique, with the opportunity to create core–shell structures, , (iii) only elastic scattering occurs up to ∼20 eV electron kinetic energy, and the droplet is optically transparent, and (iv) the mean of the droplet size distribution can be varied with angstrom resolution. Due to He-dopant Pauli repulsion, dopants that reside inside the droplet keep a constant distance to the surrounding He layer, forming a void or bubble.…”
Section: Introductionmentioning
confidence: 99%
“…He N are nanometer-sized superfluid containers that can be loaded with a wide variety of dopant atoms or molecules to study electron–atom/molecule–photon interactions inside a quantum solvent. In addition to the low temperature of 0.4 K, He N feature unique solvent properties: (i) They have the lowest influence on solvated particles both in the electronic ground state and upon photoexcitation, , (ii) they can be loaded with multiple dopant atoms and molecules by the pickup technique, with the opportunity to create core–shell structures, , (iii) only elastic scattering occurs up to ∼20 eV electron kinetic energy, and the droplet is optically transparent, and (iv) the mean of the droplet size distribution can be varied with angstrom resolution. Due to He-dopant Pauli repulsion, dopants that reside inside the droplet keep a constant distance to the surrounding He layer, forming a void or bubble.…”
Section: Introductionmentioning
confidence: 99%
“…The cold and controlled conditions provided by superfluid helium nanodroplets (He N ) enable the preparation of a wide range of otherwise inaccessible systems, as demonstrated by over three decades of frequency-domain spectroscopy 12 and mass spectrometry. 13 Concerning time-domain studies, the opportunities of He N are currently being explored and a number of photoinduced processes could be identified and characterized, including, among others, molecular alignment, 14 coherent nuclear vibration, 15–17 bond formation, 18 solvent dynamics following electronic excitation, 19–22 internal conversion, 23 quantum beats, 24 intermolecular energy transfer, 25 or nanoplasma formation. 26,27 These seminal studies have shown that, for pump–probe photoionization, the electron kinetic energy can be used as an accurate observable for processes inside He N because the helium-influence on free electrons through binary collisions is sufficiently low.…”
Section: Introductionmentioning
confidence: 99%